ASUHAN GIZI PADA ANAK MALNUTRISI, CEREBRAL PALSY, BRONKOPNEUMONIA DAN CAMPAK DI RUANG MINA RSUD HARAPAN DAN DOA KOTA BENGKULU - Yunita Yunita; Aswita Amir; Abdullah Tamrin; Titi Enyliana (Poltekkes Kemenkes Bengkulu, 2026)
Pediatric patients with infectious diseases and neurological disorders are at high risk of malnutrition due to increased metabolic needs, infection processes, and limited nutritional intake. Problem: the risk increases in patients with a history of prematurity and neuromuscular disorders such as Cerebral Palsy which can cause difficulty eating and low nutritional intake. The purpose of this study is to describe the nutritional care process for An. MFA, a 5-year-old male 8 months old with a diagnosis of measles, bronchopneumonia, Cerebral Palsy and malnutrition who was treated in the Mina Inpatient Room of Harapan dan Doa Hospital, Bengkulu City. Research method: a case study with a five-step approach of the Standardized Nutrition Care Process (PAGT), including assessment, diagnosis, intervention, monitoring, and nutritional evaluation. Anthropometric results showed poor nutritional status with a BMI/U of -3.64 SD and MUAC 64%. Dietary history showed inadequate intake because the patient since birth only consumed formula milk without additional food. Biochemical examination showed a hemoglobin level of 11.0 g/dL which is still normal. Clinical examination revealed a body temperature of 37.1°C, pulse rate of 121 beats/minute, respiratory rate of 31 breaths/minute, and SpO₂ of 99% with a general condition of moderate illness. Intervention in the form of a High Energy High Protein (TETP) liquid diet was given in stages according to the patient's clinical condition and tolerance. Monitoring over three days showed an increase in energy and nutrient intake and improvements in several clinical parameters, although anthropometric changes were not yet significant. It was concluded that planned and monitored nutritional care plays an important role in meeting nutritional needs, preventing deterioration of nutritional status, and supporting patient recovery